Future Open Networks Cross-Domain Cognitive Orchestration: A Novel Design Paradigm - Saptarshi Ghosh; Hamid Asgari; Darryl Hond; Konstantinos Antonakoglou; Ioannis Mavromatis; Noel Butler; Rasheed Hussain; Shah Zeb; Kostas Katsaros; Shadi Moazzeni; David Tee; Gabriele Incorvaia; et al. (IEEE Access)
Future Open Networks (FONs) are envisioned as large-scale, decentralised, and data-driven systems designed with open interfaces and interoperable standards to deliver diverse services and applications. The management and orchestration of these networks will utilise intelligent processing. This paper introduces a novel Cognitive Cross-Domain Orchestration (CDO) architectural framework for FONs, structured as a quad-view architecture. A background setting for the architecture is provided by a survey of relevant projects, followed by a requirements analysis for FON orchestration and management. The proposed CDO architectural framework consists of four distinct views: the Organizational View identifies stakeholders and business entities; the Functional View outlines the logical design; the Cognitive & AI/ML View connects logical functions with supportive cognitive functions for network optimization; and the System-level View links these functions to the necessary physical and intangible assets. This segregation enables each view to provide a focused analysis of the roles, interactions, and properties, thereby promoting a coherent design. The paper also describes a plausible partial proof-of-concept implementation of the CDO System-level architecture. Within the context of this CDO implementation, stakeholder participation in the provision of an end-to-end service delivery orchestrated across multiple network domains is described.